(untitled) (Future Cities and Environment, 2025)
The cultural characteristics of traditional residences in the Pearl River Delta are facing the threat of disappearance, posing a severe challenge to the inheritance and development of these architectural cultural genes. To address this crisis, this study selects Hakka traditional enclosed dwellings in Huizhou (HTEDH) as the research object, based on a literature review and field investigations. Through expert interviews, seven experts rated the importance of cultural genes in HTEDH, and a widely-adopted Analytic Hierarchy Process (AHP) was employed to establish a comprehensive memes identification and judgment matrix for HTEDH. The model categorizes the architectural cultural memes of HTEDH into four main clusters: spatial layout, exterior and structure, materials and craftsmanship, and decoration, with 35 sub-genes identified as indicators within these categories. Consistency checks and weight calculations were performed using the AHP method. Based on the calculated weights, the architectural cultural memes were ranked in terms of structure and priority. The results of this study provide an importance ranking of the architectural cultural genes of HTEDH and construct a ranking index system. Additionally, questionnaires were distributed to local residents to obtain the proportion of liking for each architectural cultural gene of HTEDH. The research method and results, which combine importance ranking with public preference, provide a foundation and decision-making reference for protecting residential cultural memes in the Pearl River Delta region. The proposed ranking offers an appropriate evaluation criterion for applying architectural genes in rural landscape conservation and development, facilitating the inheritance and development of traditional residential architectural cultural memes.